Precursor feeding for enhanced production of Secondary metabolites: A review - A. G, Namdeo; T. S, Jadhav; P. K, Rai; S, Gavali; K. R, Mahadik (Pharmacognosy Reviews)
Medicinal plants are unique sources of pharmaceutically significant secondary metabolites which include alkaloids, glycosides, flavonoids, volatile oils, tannins, resins etc. Demands of these secondary metabolites are not readily accomplished because of their low yield in intact plants, environmental, geographical and/or governmental restrictions. Chemical synthesis or semisynthesis of these metabolites are either extremely difficult or economically infeasible because of their highly complex structures and stereospecific chemical nature. Plant cell culture is an attractive alternative, but to date this has had only limited commercial success. Precursor feeding has been a successful approach for enhanced production of secondary metabolites from plant cells grown in vitro. Present review summarizes the application of precursor feeding for enhanced production of secondary metabolites from plant cells.
Keywords: Pharmaceuticals; precursor; precursor feeding; secondary metabolites